Chingonas and Chingados: Femininity and Machismo in Three Poems by Francisco X. Alarcón - Garcia Iglesias, Jaime (Complutense Journal of English Studies, 2017)
This article analyzes the ways in which Queer Chicano poet Francisco X. Alarcón presents the interplay of family, sexuality, and heritage in his poetry. Three poems are analyzed: “Cuarto oscuro/Dark Room”, “Mi padre/My Father”, and “Una pequeña gran victoria/A Small but Fateful Victory”. In these pieces, Alarcón negotiates his own identity as an ‘Other’ of the Chicano Community by emphasizing the performative nature of masculinity and femininity. In so doing, he provides an insight into the dilemmas and fractures of contemporary Chicanos. Thus, this piece aims to also incorporate Alarcón to the Chicano literary canon by studying how his poems echo the theoretical paradigms established by Anzaldúa, Arteaga, and others.